2022
DOI: 10.1038/s41380-022-01660-1
|View full text |Cite
|
Sign up to set email alerts
|

Induced neural progenitor cells and iPS-neurons from major depressive disorder patients show altered bioenergetics and electrophysiological properties

Abstract: The molecular pathomechanisms of major depressive disorder (MDD) are still not completely understood. Here, we follow the hypothesis, that mitochondria dysfunction which is inevitably associated with bioenergetic disbalance is a risk factor that contributes to the susceptibility of an individual to develop MDD. Thus, we investigated molecular mechanisms related to mitochondrial function in induced neuronal progenitor cells (NPCs) which were reprogrammed from fibroblasts of eight MDD patients and eight non-depr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 59 publications
10
52
0
Order By: Relevance
“…We then reprogrammed the fibroblasts to induced pluripotent stem cells (iPSCs) which we subsequently differentiated to neural progenitor cells (NPCs) and neurons. Like in peripheral cells, we observed signs of altered mitochondrial function in the neural lineage including lower respiration rates 30 . In neurons, electrophysiological measurements showed significantly lower membrane capacitance, a more depolarized membrane potential, and increased spontaneous electrical activity 30 .…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…We then reprogrammed the fibroblasts to induced pluripotent stem cells (iPSCs) which we subsequently differentiated to neural progenitor cells (NPCs) and neurons. Like in peripheral cells, we observed signs of altered mitochondrial function in the neural lineage including lower respiration rates 30 . In neurons, electrophysiological measurements showed significantly lower membrane capacitance, a more depolarized membrane potential, and increased spontaneous electrical activity 30 .…”
Section: Introductionmentioning
confidence: 58%
“…Like in peripheral cells, we observed signs of altered mitochondrial function in the neural lineage including lower respiration rates 30 . In neurons, electrophysiological measurements showed significantly lower membrane capacitance, a more depolarized membrane potential, and increased spontaneous electrical activity 30 .…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Cerebrospinal fluid (CSF) level of MMP2 was significantly higher in patients with major depression [62] while peripheral levels of MMP2 were significantly lower in patients with mood disorders [63]. A recent study showed that iPSC-derived NPCs and neurons from MDD patients had decreased basal respiration and increased spontaneous electrical activity, respectively [64]. iPSC-derived GABA interneurons from suicide attempters with major depression showed increased neurite branches, electrophysiological hyperexcitability, and decreased calcium signaling [65].…”
Section: Discussionmentioning
confidence: 99%
“…On-going efforts are identifying other mechanisms by which variants impact gene regulation, such as through detection of chromatin QTLs, cell fraction QTLs, and chromatin conformational changes 22 . Psychiatric disorders have also been associated with changes in diverse cellular phenotypes such as cell adherence [23][24][25] , cellular energetics 26,27 , and neuron electrophysiological response patterns 26,28 . In a limited number of cases, causal links between psychiatric genetic variants and changes in cellular phenotypic variation have been established.…”
Section: Introductionmentioning
confidence: 99%